2019
DOI: 10.1007/s00259-019-04402-8
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid PET/MRI in major cancers: a scoping review

Abstract: Research, University of Southern Denmark are acknowledged for help with the literature search.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 36 publications
0
20
5
Order By: Relevance
“…Considering the results of the present study, which showed the superiority of 18 F-FDG PET/MRI to ceCT for M staging, 18 F-FDG PET/MRI might offer a useful alternative imaging modality to ceCT, or 18 F-FDG PET/CT in the assessment of N and M staging as well as in the T staging in ovarian cancer. We could not show the superiority of 18 F-FDG PET/MRI over ceCT for N staging, although previous reports have suggested the superiority of 18 F-FDG PET/MRI compared with conventional modalities in other cancers (25). A possible reason for this lack of difference could be the small number of events and samples in our study.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Considering the results of the present study, which showed the superiority of 18 F-FDG PET/MRI to ceCT for M staging, 18 F-FDG PET/MRI might offer a useful alternative imaging modality to ceCT, or 18 F-FDG PET/CT in the assessment of N and M staging as well as in the T staging in ovarian cancer. We could not show the superiority of 18 F-FDG PET/MRI over ceCT for N staging, although previous reports have suggested the superiority of 18 F-FDG PET/MRI compared with conventional modalities in other cancers (25). A possible reason for this lack of difference could be the small number of events and samples in our study.…”
Section: Discussioncontrasting
confidence: 77%
“…In terms of 18 F-FDG PET/MRI, no reports appear to have described the assessment of N and M staging for ovarian cancer. In other cancers, including nasopharyngeal, breast, and colorectal cancers, 18 F-FDG PET/MRI has been reported as superior compared with 18 F-FDG PET/CT for detecting lymph nodes or distant metastasis (25). Moreover, 18 F-FDG PET/MRI has been reported as equivalent to MRI in cervical cancer (22) for the detection of lymph nodes or distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the results of the present study, which showed the superiority of 18 F-FDG PET/MRI to ceCT for M staging, 18 F-FDG PET/MRI might offer a useful alternative imaging modality to ceCT, or 18 F-FDG PET/CT in the assessment of N and M staging as well as in the T staging in ovarian cancer. We could not show the superiority of 18 F-FDG PET/MRI over ceCT for N staging, although previous reports have suggested the superiority of 18 F-FDG PET/MRI compared with conventional modalities in other cancers (27). A possible reason for this lack of difference could be the small number of events and samples in our study.…”
Section: Discussioncontrasting
confidence: 77%
“…In terms of 18 F-FDG PET/MRI, no reports appear to have described the assessment of N and M staging for ovarian cancer. In other cancers, including nasopharyngeal, breast, and colorectal cancers, 18 F-FDG PET/MRI has been reported as superior compared with 18 F-FDG PET/CT for detecting lymph nodes or distant metastasis (27). Moreover, 18 F-FDG PET/MRI has been reported as equivalent to MRI in cervical cancer (24) for the detection of lymph nodes or distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…These studies demonstrated a high predictive value of post therapy FDG uptake [8]. Radiotherapy planning studies using [ 18 F]-FDG-PET/CT or [ 18 F]-FDG-PET/MRI resulted in an improved detection of the gross tumour volume (GTV) in comparison with structural imaging (either CT or MRI) alone [9][10][11]. On the other hand, the limitations of [ 18 F]-FDG-PET have to be considered when it comes to the specificity of the uptake since several structures in the neck show physiological or inflammation-related uptake of glucose influencing the correct contouring of the tumour significantly [9].…”
mentioning
confidence: 99%